Comparative Biomechanical Study Between Shooting with Two Points and Three Points from Specific Areas Inside and Outside the Basketball Shooting Area - Ibrahim, Moataz Khalil (Pubmedia Jurnal Pendidikan Olahraga, 2024)
The aim of the current research is to identify the relationships and significance of differences in displacements, horizontal and vertical velocities for the strength and accuracy of shooting by jumping with two and three points from specific areas inside and outside the basketball shooting zone at the moment of pivot. It also aims to identify the relationships and significance of differences in displacements, horizontal and vertical velocities for the strength and accuracy of shooting by jumping with two and three points from specific areas inside and outside the basketball shooting zone at the moment of shooting. The research methodology utilized a descriptive approach using survey studies with their tools and procedures, relying on video analysis as it suited the nature of the research. The research sample consisted of three players who were purposely selected to be similar in physical characteristics and skilled in shooting a basketball. Each player performed 10 attempts, divided into five two-point and five three-point shooting attempts. The best three attempts for each player in both types of shooting, which achieved the highest level of accuracy according to the test, were selected from specific areas inside and outside the basketball shooting zone. Thus, the actual attempts subjected to statistical processing were 18 attempts, divided into nine attempts for shooting with two points from areas within the shooting zone and nine attempts for shooting with three points from specific areas outside the shooting zone. The researcher concluded that the logarithmic differences between correlation coefficients for horizontal and vertical displacements and velocities for the strength and accuracy of shooting by jumping with two and three points from specific areas inside and outside the basketball shooting zone favored shooting with three points. Also, the logarithmic differences between correlation coefficients for horizontal and vertical velocities for the strength and accuracy of shooting by jumping with two and three points from specific areas inside and outside the basketball shooting zone favored shooting with three points.